Effects of viscous dissipation on natural convection flow along a sphere with radiation and heat generation - Aktar, Salina; Ruma, Mahmuda Binte Mostafa; Alim, M. A. (Journal of Naval Architecture and Marine Engineering, 2013)
The effects of viscous dissipation on free convection flow along a sphere with radiation and heat generation have been investigated in this paper. The governing equations with associated boundary conditions for this phenomenon are converted to dimensionless forms using a suitable transformation. The transformed non-linear equations are then solved using the implicit finite difference method. Numerical results of the velocity and temperature profiles, skin friction coefficient and surface temperature profiles for different values of the of viscous dissipation parameter Vd ( 0.0 to 4.0), radiation parameter Rd (0.0 to 1.0), the Prandlt number Pr (0.72 to7.0)and the heat generation parameter Q (0.2 to 0.6) are presented graphically. Detailed discussion is given for the effects of the aforementioned parameters. Significant effect is found in the velocity and temperature profiles, skin friction coefficient and surface temperature distribution for the Prandtl number, heat generation and radiation parameters. DOI: http://dx.doi.org/10.3329/jname.v10i1.12809